2020
DOI: 10.1007/s10100-020-00710-9
|View full text |Cite
|
Sign up to set email alerts
|

An optimisation approach for the e-grocery order picking and delivery problem

Abstract: Traditional supermarket chains that are adopting an omni-channel approach must now carry out the order picking and delivery processes to serve online orders, previously done by the customer. The complexity of the logistics processes has increased, therefore modelling and optimising e-grocery operations becomes definitely important. Since there are few studies modelling order picking and delivery processes, we propose an approach that simultaneously optimises the decision variables of different functions which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…The essence is that for e-grocery services to be sustainable-both in terms of being profitable for e-grocers and in terms of their impact on the environment-they need to operate at scale. Otherwise, delivery vans drive around half-empty and/or have to navigate Sustainability 2021, 13, 4144 2 of 27 suboptimal routes [15,16]. COVID-19 has forced many people around the world to use an online grocery service for the first time or, for those who had already adopted it, rely on it more than before [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The essence is that for e-grocery services to be sustainable-both in terms of being profitable for e-grocers and in terms of their impact on the environment-they need to operate at scale. Otherwise, delivery vans drive around half-empty and/or have to navigate Sustainability 2021, 13, 4144 2 of 27 suboptimal routes [15,16]. COVID-19 has forced many people around the world to use an online grocery service for the first time or, for those who had already adopted it, rely on it more than before [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, some studies identified that operational costs are a key factor in the profitability of the new channel (Holzapfel et al 2016;Valle and Beasley 2020). Therefore, e-grocers should focus on improving delivery efficiency to reduce logistics costs and product quality loss (Darestani and Hemmati 2019;Vazquez-Noguerol et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, online grocery initiatives are proliferating, and both start-ups and big dotcoms are entering the market (MacCarthy et al, 2019). On the other hand, in the realm of the coronavirus disease 2019 (COVID-19) emergency, many previously sceptical customers have experienced online purchases and are now inclined to change their grocery shopping behaviour in favour of e-commerce (Vazquez-Noguerol et al, 2020). In this scenario, traditional grocery retailers have started to offer e-commerce services to stay competitive (Li et al, 2021).…”
mentioning
confidence: 99%
“…As a result, they implement this solution only when their online volumes are significant enough and prefer, in the initial stages of the business, to manage operations in physical stores (MacCarthy et al, 2019). Based on the above, numerous grocery retailers are striving to find an efficient and effective way to keep up with the rapid evolution of e-commerce by leveraging their stores without investing a huge amount of resources (Vazquez-Noguerol et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation